Är kraven i TDOK motiverade? - Nordvall,Anton (2017)
In the regulation of Trafikverket there is many technical requirements that the railway facility should face. The reason for its existence is to create a standardized facility with well balanced requirements that includes implementation and management. But still, sometimes there is a need for violating some requirements, for example when the motive of the requirements are not holding against the motive of the violations. Furthermore there is a possibility that some questions and uncertainties comes along the requirements. This very topic is what the report is about, i.e. to investigate how two technical requirements that belongs to the regulation of Trafikverket are holding against the reality. By reality for one requirement it means incorrect statistics and for the other it means what knowledgeable people say is the most appropriate thing. The report is divided in to two parts where each part includes one requirement. Within each part there is several questions that will be answered. The parts and the questions are as follows: 1. Rail transitions in curves There is a requirement that limits the curve radius to 1500 meters for rail transitions, why? Are there any arguments that can be used to violate the requirement in a dispensation application? Is the requirement motivated? Are there any other geometries than this curves that is in more need for a regulation? 2. Neutralization against switches How close is it possible to neutralize against switches to affect their components as little as possible? Are there any difference to neutralize against FSK respective BKS in a switch? Is the requirement of Trafikverket, that says the most favourable for the switch that you shouldn’t place the cape or move closer than 20 meters from the FSK/BKS, correct? And finally, is the requirement motivated? To investigate the first part incorrect statistics primarily been used. Computer system as BIS, Ofelia and BESSY been applied to solve where the rail transitions are located and how the incorrect statistics differ with the curve radius. It turned out that the requirement that says you should not place rail transitions in curves with radius less than 1500 meters can not be motivated by incorrect statistics. To investigate the second part knowledgeable people that has years of experience in track and track forces has been interviewed. The answers got compiled and and later compared to each other and some earlier studies. The neutralization requirement can finally be motivated because the answers of the interviews is unambiguous, i.e. you should not neutralization close to switches.
Keywords: övergångsräler; neutralisering; växlar; trafikverket; intervjuer; felstatistik